A new approach to improve the accuracy of DGT (Diffusive Gradients in Thin-films) measurements in monitoring wells - Santos, Cristiane Aily [UNESP]; Gemeiner, Hendryk [UNESP]; Menegário, Amauri Antonio [UNESP]; Galceran, Josep; Zanatta, Melina Borges Teixeira [UNESP]; Chang, Hung Kiang [UNESP] (Elsevier, 2022)
The Diffusive Gradients in Thin-films (DGT) technique represents an ideal tool for monitoring water quality of inorganic species in systems with a high flow such as rivers, streams, lakes and seas. However, in low-flow systems (non-turbulent waters), the influence of a diffusive boundary layer (DBL) formed on the surface of the DGT device has been observed, which can lead to erroneous measurements by DGT. Therefore, the use of DGT in wells for groundwater monitoring is still very limited until now. In this sense, the present study evaluates the applicability of the DGT technique in non-turbulent and low-flow water systems. We propose a new way to calculate the DBL with the objective to carry out a robust DGT analysis in environmental monitoring wells. For this purpose, DGT devices with different diffusive gel thicknesses were deployed in an experimental set-up simulating a groundwater monitoring well. A DBL thickness (for each element) was calculated from the slopes of the linear regressions between the DGT accumulated mass of metal and the deployment time (4, 8, 12, 24 and 48 h) for each of the two diffusive gel thicknesses. The mean DBL thickness (averaging the individual DBL thicknesses calculated from the slopes) was 0.06 cm. The concentrations of the analysed elements were corrected with this DBL with the result that the metal concentrations measured by DGT improved and were highly approximated to their actual total values in this non-complexing medium.
Keywords: DBL; Diffusive gradients in thin-films; Groundwater monitoring; Stagnant waters; Well